A Simple Procedure for Accurate Quantitation of Factor VIII Inhibitors - Tse, Daphne; Fekete, L; Shanbrom, E (Thrombosis and Haemostasis, 1970)
A simple assay for quantitative determination of factor VIII (AHF) inhibitors has been developed. The presence of AHF inhibitor is confirmed by determining clotting time in serial dilutions of patient’s plasma. The amount of inhibitor is then quantitat-ed by adding known units of human AHF concentrate (1 to 100 units/ml) to plasma until neutralization occurs. The neutralization point is defined as that level of AHF concentrate which clots the patient’s plasma in the same time as the control plasma (inhibitor-free) would clot in the presence of 1 unit of AHF concentrate. (This point, minus the initial 1 unit/ml, gives the titer of inhibitor present (units/ml). The dosage of AHF concentrate required to overcome the inhibitor and raise the free circulating AHF to the desired theoretical level is then calculated from the known titer of inhibitor. This method has been evaluated by assays of 75 samples from 22 patients with acquired or induced AHF inhibitors. In vivo plasma AHF activity correlated well with the calculated in vitro values. The assay provides reliable and accurate quantitation of factor VIII inhibitors enabling precise calculation of effective AHF dosage and monitoring of therapeutic response. The assay can be readily adapted to quantitation of other clotting factor inhibitors.